Promising tacrine/huperzine A‐based dimeric acetylcholinesterase inhibitors for neurodegenerative disorders: From relieving symptoms to modifying diseases through multitarget. Issue 6 (5th July 2021) - Mak, Shinghung; Li, Wenming; Fu, Hongjun; Luo, Jialie; Cui, Wei; Hu, Shengquan; Pang, Yuanping; Carlier, Paul R.; Tsim, Karl Wahkeung; Pi, Rongbiao; Han, Yifan
Abstract: Neurodegenerative disorders, such as Alzheimer's disease and Parkinson's disease, are devastating diseases in the elderly world, which are closely associated with progressive neuronal loss induced by a variety of genetic and/or environmental factors. Unfortunately, currently available treatments for neurodegenerative disorders can only relieve the symptoms but not modify the pathological processes. Over the past decades, our group by collaborating with Profs. Yuan‐Ping Pang and Paul R. Carlier has developed three series of homo/hetero dimeric acetylcholinesterase inhibitors derived from tacrine and/or huperzine A. The representative dimers bis(3)‐Cognitin (B3C), bis(12)‐hupyridone, and tacrine(10)‐hupyridone might possess disease‐modifying effects through the modulation of N ‐methyl‐d ‐aspartic acid receptors, the activation of myocyte enhancer factor 2D gene transcription, and the promotion of neurotrophic factor secretion. In this review, we summarize that the representative dimers, such as B3C, provide neuroprotection against a variety of neurotoxins via multiple targets, including the inhibitions of N ‐methyl‐d ‐aspartic acid receptor with pathological‐activated potential, neuronal nitric oxide synthase, and β‐amyloid cascades synergistically. More importantly, B3C might offer disease‐modifying potentials by activating myocyte enhancer factor 2D transcription, inducing neuritogenesis, and promoting the expressions of neurotrophic factors in vitro and in vivo. Taken together, the novel dimers might offer synergistic disease‐modifying effects, proving that dimerization might serve as one of the strategies to develop new generation of therapeutics for neurodegenerative disorders. Abstract : Over the past decades, several series of homo/hetero dimeric acetylcholinesterase (AChE) inhibitors derived from tacrine and/or huperzine A have been developed. In this review, we summarize that the representative dimers, such as bis(7)‐cognitin (B7C) and bis(3)‐cognitin (B3C), provide neuroprotection against a variety of neurotoxins via multiple targets, including the inhibitions of neuronal nitric oxide synthase (nNOS), N‐methyl‐D‐aspartic acid (NMDA) receptor with pathological‐activated potential and β‐amyloid cascades synergistically. More importantly, B3C might offer disease‐modifying potentials by activating Myocyte enhancer factor 2D (MEF2D) transcription, inducing neuritogenesis, and promoting the expressions of neurotrophic factors in vitro and in vivo, proving that dimerization might serve as one of the strategies to develop new generation of therapeutics for neurodegenerative disorders.